Reverse Logistics model for Horticultural packaging at the proposed facility - Rajendran, Santhosh (2010)
The Indian horticulture distribution sector is comprised of companies that sell products in the wholesale market and are geographically established outside rural warehouses and markets, although many of these companies are located very near them.The horticulture market lacks packages that are palletizable and modular, appropriate for different products, clean, cheap, and if returnable, with a guarantee of return and disinfection, with guaranteed availability, and when empty; do not enter the commercialization area. The capacity of managing returns has been considered as an important competitiveness factor of companies. This is especially important for the food industry given the high perishability of its products and the complexity of its distribution channel. These factors combined make critical the relation between the members of the distribution channel. Traditionally, the products flow in a distribution channel happens from the industry towards the final consumer. However, some factors such as defective products, or damaged, date expired, recyclable, order errors cause a flow in the opposite sense, what generates the need for a logistics operation called reverse. With this emergent project in mind, this paper aims at presenting the reverse logistics model proposal for horticulture packages used at the proposed facility mentioned in the business plan.